2022
DOI: 10.1186/s12889-022-13595-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of digital stories as a health promotion intervention: a scoping review

Abstract: Background It is challenging to develop health promotion interventions created in collaboration with communities affected by inequities that focus beyond individual behavior change. One potential solution is interventions that use digital stories (DS). Digital storytelling (DST) is an opportunity for reflection, connection with others, and the elevation of voices often absent from daily discourse. Consequently, public health researchers and practitioners frequently employ the DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…We examined the feasibility, acceptability, and preliminary effects of the DST intervention on vaccination attitudes and intention among a community sample of 50 Korean American and 114 Vietnamese American mothers of unvaccinated children. Although prior research examining DST interventions has demonstrated their potential benefits for promoting a variety of health behaviors among youth and adult participants [ 21 , 31 ], limited research has used this type of low-cost, scalable, and accessible approach, which can be tailored to culturally and linguistically appropriate ways to match mothers’ concerns, to address the low HPV vaccination rates in Korean American and Vietnamese American adolescent boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the feasibility, acceptability, and preliminary effects of the DST intervention on vaccination attitudes and intention among a community sample of 50 Korean American and 114 Vietnamese American mothers of unvaccinated children. Although prior research examining DST interventions has demonstrated their potential benefits for promoting a variety of health behaviors among youth and adult participants [ 21 , 31 ], limited research has used this type of low-cost, scalable, and accessible approach, which can be tailored to culturally and linguistically appropriate ways to match mothers’ concerns, to address the low HPV vaccination rates in Korean American and Vietnamese American adolescent boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to more traditional channels (e.g., social media ads, digital ads, and radio/TV ads), there are expanded opportunities for promoting health benefits of self-care via connected TV (CTV) ads, digital magazines, and podcasts. Video-and audiobased channels can be used for digital storytelling, which has already been used as education, marketing, empowerment, and health promotion tools (108)(109)(110)(111). It is noteworthy that multimedia communications enable more effective outreach covering diverse demographics and interest groups.…”
Section: Health Promotion Education and Empowermentmentioning
confidence: 99%
“…Furthermore, a recent study by Lohr et al, (2022) emphasized that with the emergence of various social media platforms, oral storytelling evolved into digital storytelling, providing an opportunity for reflection, connection with others, and the elevation of voices that are often absent from the daily discourse. Digital storytelling incorporates technology, comprising various multimedia modes such as graphics, audio, texts, videos, and animations (Choo et al, 2020).…”
Section: Hope Intervention Towards Orphan Of Covid-19mentioning
confidence: 99%